Cell culture-based biosensing techniques for detecting toxicity in water. (June 2017) - Tan, Lu; Schirmer, Kristin
Graphical abstract: Highlights: Impedance & chromatophore-based methods are leading cell culture-based techniques. Mammalian & fish cells are used in biosensors; fish cells are more robust & stable. Cell models are able to respond to a broad spectrum of substances in water samples. Real-time, combinatorial/multiparametric biosensors are among the major trends. Bridging legislation & exploring proprietary/commercialisation routes will promote application. Abstract : The significant increase of contaminants entering fresh water bodies calls for the development of rapid and reliable methods to monitor the aquatic environment and to detect water toxicity. Cell culture-based biosensing techniques utilise the overall cytotoxic response to external stimuli, mediated by a transduced signal, to specify the toxicity of aqueous samples. These biosensing techniques can effectively indicate water toxicity for human safety and aquatic organism health. In this review we account for the recent developments of the mainstream cell culture-based biosensing techniques for water quality evaluation, discuss their key features, potentials and limitations, and outline the future prospects of their development.